?STUDIES ON REHYDRATION OF VEGETABLES - BEG, MIRZA ARSHAD ALl; MUHAMMAD, NAZAR; ANwAR, M.; MUDDIN, A.F.M.EIITESHA (Biological Sciences - PJSIR, 1995)
Rehydrationcapacitiesofcabbage,potato,turnipandonion,whendehydratedat37°C tovariouslevelsofhydration, were studied. None of the vegetables, dehydrated toany degree,exhibited 100%rehydration.The greater thedegree of dehydration, theJesscomplete wasthedegree of rehydration, There seems to exist a critical point during dehydration of each vegetable beyond which a significantlossin rehydrationcapacityisapparent.These points forcabbage, potato, turnip andonion were respectively43,31,63 and45% oftheirfreshweight.Dehydrationtomore than40% of thefresh weight inactivated the reducing enzyme of respiring system. Reasons for the failure of dehydrated tissue to regain the original weight have been discussed in terms of events that affect the structure and function of cellular components.